Ø§Ù„ÙÙ„Ø³ÙØ© ÙˆØ§Ù„ØªØµÙˆÙ ÙÙŠ ÙÙƒØ± ØØ¬Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ø£Ø¨ÙŠ ØØ§Ù…Ø¯ Ø§Ù„ØºØ²Ø§Ù„ÙŠ - Ali, Isa Abdullah (IAIN Surakarta, 2017)
This article attempts to explain the efforts of Abu Hamid al Ghazali in bringing together two poles; philosophy and taá¹£awwuf, between reason and revelation, between spiritual and intellectual. This is the widely misunderstood by many researchers; the allegations that al-Ghazali is the estuary of stagnancy of progressive thinking is a hasty and reckless accusation. In this article, the author finds that al Ghazali's philosophical passion has begun since he was very young; much of al Ghazali's work is a testament to this. Then, although shifted to the realm of taá¹£awwuf, the influence of philosophy is still very subtle in the rhetoric of his writings. The depth of Ghazali's knowledge in Fiqh Shafi'i becomes another proof of the combination of reason and revelation in Ghazali's thoughts coupled with the Ash'ariyya school which he purports as his theological foundation.Â Â Keywords:Abu Hamid al Ghazali, Taá¹£awwuf, Philosophy